Total Quality Management Applications in the Process of Qualifying and Training Physical Education Teachers - Alwan , Qutaiba (Journal of Physical Education, 2024)
The importance of the research here comes as an initial initiative that may represent in its results a basis for comparison between everything new and modern in the world of training and qualification and traditional methods in training operations, through knowing what is the possibility of applying the principles of total quality management in training and through the opinions and viewpoints of those in charge of the training process from administrators and trainers in the education directorates in different regions of Iraq, as they are the closest to the existing reality.    It is also worth noting that most researchers who have addressed the topic of total quality management and its applications have greatly enriched their research with the concept of total quality, but their studies and research that they conducted did not address the relationship of the training process to the concept of total quality management, especially with regard to training various teaching cadres and the specialization of physical education in particular. Accordingly, the researcher did not find (according to his knowledge) any studies that addressed this topic, which represents great importance in the success of the work of the educational institution. The problem of the research lies in the clear delay in the level of the process of qualifying and training physical education teachers through the qualifying courses held by the Educational Preparation and Training Department in the Ministry of Education and the importance of applying the comprehensive quality strategy and trying to employ it in the aforementioned training and qualification processes. The research aims to identify the degree of importance of applying the comprehensive quality management strategy in the process of training and qualifying physical education teachers . The research is limited to the directors and directorates of preparation and training and the governorates of central and southern Iraq, as well as a section of specialized professors and specialized supervisors who represent the training cadres accredited by these directorates and the governorates themselves and for the academic year (2023/2024). The research community consists of (9) directors of preparation and training in the Ministry of Education in the governorates of central and southern Iraq and (14) professors and specialists in the field of physical education and training programs, so that the research community became composed of (23) of the aforementioned categories . After that , the researcher designed the scale in a manner that is compatible with the research sample and used the scientific foundations and appropriate statistical methods that produced the scale in its final form with (27) paragraphs. The scale was applied to the research sample and the most important results of the study were: By coming up with a number of results, the most important of which was the application of modern training and educational techniques in teaching physical education, as well as the great support in various fields for trainees and trainers. The researcher also came up with a set of recommendations and proposals, the most important of which was the necessity of selecting competent and unique elements who have the ability and knowledge in modern teaching techniques according to the perspective of comprehensive quality as leaders. An administrative body based on the training process, as well as establishing and activating departments for comprehensive quality management in all training centers for training teachers and for various specializations within the Ministry of Education.